The impact of COVID-19 lockdown on sleeping pattern among college students in an urban setting - Ramakrishnan, Arun Ram; Rajaram, Dinesh (International Journal Of Community Medicine And Public Health, 2025)
Background: The COVID-19 pandemic created a unique scenario where the public were confined to their homes through systemic lockdown. This study was envisaged to identify and analyse any potential changes in the sleeping pattern of college going students during lockdown by comparing with the patterns before lockdown. Methods: This study was a retrospective study (record analysis). The survey to collect the primary data was made on google forms and distributed through various social media platforms such as WhatsApp, Facebook and Instagram. The records contained data obtained from college going students studying in urban educational institutions. All participants were between the age of 18 and 30 regardless of gender, religion, caste etc. The data was analysed using SPSS Software using Mcnemar’s test for comparison of sleep quality pre-lockdown and during lockdown. Results: It was observed that the study participants were sleeping later in the night and waking earlier in the morning during lockdown as compared to pre-lockdown. The sleep onset time has also shifted to a longer duration during lockdown. Actual hours slept at night has shifted to less than 7 hours in nearly 10% of the study population. Conclusions: The study participants were sleeping later in the night and waking earlier in the morning during lockdown as compared to pre-lockdown with a more significant change in waking time during lockdown. The sleep onset time has also shifted to longer duration during lockdown actual hours slept at night has shifted to less than 7 hours in nearly 10% of the study population.